Geochemical Characterization of Magma Source(s) and Compositional Variation within the Incrementally Emplaced Jackass Lakes pluton, Sierra Nevada Batholith, California. - Stanek, Heidi L. (My University, 2009)
Previous field research in the Jackass Lakes pluton described this ~98 Ma intrusion as being emplaced as a series of magma increments. This study examines a suite of 52 samples that represent all described plutonic units within the pluton.
Color poster with text, diagrams, and maps describing research conducted by Heidi L. Stanek, advised by Geoffrey S. Pignotta.
Keywords: Intrusions (Geology)--California--Jackass Lakes; Magmas--California--Jackass Lakes; Geochemistry--California--Jackass Lakes; Batholiths--Sierra Nevada (Calif. and Nev.); Posters